Analysis of Internal Business Communication In Improving Work Motivation - Octaviar Wilmar Ervanni; Havis Aravik; Choiriyah, Choiriyah; Fadilla, Fadilla; Dwi Noviani (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2025)
This study explores the role of internal business communication in enhancing work motivation within a creative agency. The primary goal is to investigate how open, collaborative, and visual communication practices can improve creative motivation among team members. The research adopts a qualitative approach through a case study, utilizing observations, in-depth interviews with staff and managers, and analysis of internal documents such as weekly reports and brainstorming notes. The results indicate that effective communication, particularly through collaborative discussions, recognition of the creative process, and the use of visual and nonverbal tools, significantly boosts motivation and creativity within teams. Participants noted that the encouragement of open dialogue and idea-sharing fostered a sense of ownership and pride in their work, driving them to contribute innovative ideas. Furthermore, regular appreciation of the process rather than just the outcome helped sustain intrinsic motivation. This study highlights the importance of managing internal communication to create a work environment that nurtures creativity and productivity, offering practical insights for organizations looking to improve their internal communication strategies and enhance team performance.